Controle das vibrações de rotores flexíveis pela introdução de forças externas, através de técnicas de otimização - Oliveira, Ademyr Gonçalves de (1994)
This work presents an alternative open loop control method of flexible rotors vibration levei, through the introduction of externai forces to a rotating machine, straight along the rotors. Such forces, its number and distribution along the rotors, are selected observing the system modal information. The forces are defined by the following parameters: amplitude, frequency of excitation and angle of actuatíon and are determined through numerical optimization techniques, in a way which minimizes the system deformation energy. The rotor is modeled through the transfer matrix method where gyroscopic system eigenvalues are obtained through a polynomial method. The steady-state response of the system is calculated by a modal method. Numerical simulation shows a reductions up to 90% of the deformation energy of the shaft-bearings system, what indicates a significant reduction on the vibration levei.